The Influence of Transformational Leadership and Work Discipline on the Performance of Employees in the Assembling and Sewing Sections at PT Adis Dimension Footwear, Tangerang Regency - Safitri, Nur; Fahmi, Khaerul; Setiawan, Temmy (IJOSPOL - International Journal of Social, Policy and Law, 2026)
This study aims to determine: (1) the partial effect of transformational leadership on employee performance; (2) the partial effect of work discipline on employee performance; (3) the simultaneous effect of employee competence and work discipline on employee performance. This study uses a quantitative descriptive method, which describes variables as they are, supported by numerical data generated from actual conditions. The population in this study was all employees in the Assembling and Sewing departments at PT. Adis Dimension Footwear Balaraja-Tangerang. The research sample consisted of 61 respondents. The technique used to determine the sample in this study was simple random sampling. Meanwhile, to determine the representative sample size in quantitative research, the Slovin formula was used. Data analysis used multiple linear regression analysis with SPSS 26. The results of this study indicate that (1) partially, transformational leadership significantly influences the performance of Assembling and Sewing employees at PT. Adis Dimension Footwear Balaraja-Tangerang, which is indicated by the calculated t value> t table (2.407>2.002) and the significance value of 0.000 is smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (2) Partially, work discipline significantly influences the performance of Assembling and Sewing employees at PT. Adis Dimension Footwear Balaraja-Tangerang, which is indicated by the calculated t value> t table (4.836>2.002) and the significance value of 0.000 is smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (3) Simultaneously, transformational leadership and work discipline significantly influence the performance of Assembling and Sewing employees at PT. Adis Dimension Footwear Balaraja-Tangerang, which is indicated by F count> F table (19.277>3.16) with a significance level of 0.000. Thus Ha is accepted and H0 is rejected. Based on the research results, it can be concluded that transformational leadership and work discipline variables, both partially and simultaneously, have a significant influence on the performance of Assembling and Sewing employees at PT. Adis Dimension Footwear Balaraja-Tangerang.